Differential Roles of Peroxisome Proliferator-Activated Receptor-α and Receptor-γ on Renal Crystal Formation in Hyperoxaluric Rodents. (28th February 2016) - Taguchi, Kazumi; Okada, Atsushi; Hamamoto, Shuzo; Unno, Rei; Kobayashi, Takahiro; Ando, Ryosuke; Tozawa, Keiichi; Gao, Bing; Kohri, Kenjiro; Yasui, Takahiro
Abstract : Peroxisome proliferator-activated receptors (PPARs) and related inflammatory and oxidative molecule expression were investigated in a hyperoxaluric rodent model to evaluate the in vivo efficacy of PPAR agonists in preventing renal crystal formation. PPAR expression was examined in a mouse hyperoxaluria kidney stone model induced by daily intra-abdominal glyoxylate injection. Therapeutic effects of the PPAR α agonist fenofibrate and PPAR γ agonist pioglitazone were also assessed in a 1% ethylene glycol-induced rat model of hyperoxaluria. Crystal formation, inflammation, cell injury, apoptosis, and oxidative stress were compared to those of vehicle-treated controls. Quantitative reverse transcription-polymerase chain reaction revealed that PPAR α and PPAR γ expression decrease and increase, respectively, during crystal formation in hyperoxaluric kidneys. In addition, PPAR α localized to the cytoplasm of both proximal and distal tubular cells, whereas PPAR γ accumulated in the nucleus of proximal tubular cells. Furthermore, renal crystal formation was significantly less prevalent in pioglitazone-treated rats but higher in the fenofibrate-treated and fenofibrate/pioglitazone-cotreated groups compared to controls, thus indicating that pioglitazone, but not fenofibrate, markedly decreased cell inflammation, oxidative stress, and apoptosis. Collectively, the results demonstrated that PPAR γ suppressed renal crystal formation via its antioxidative and anti-inflammatory effects; however, the renotoxicity of PPAR α may elicit the opposite effect.